2015
DOI: 10.1182/blood-2014-08-593343
|View full text |Cite
|
Sign up to set email alerts
|

Sp1/Sp3 transcription factors regulate hallmarks of megakaryocyte maturation and platelet formation and function

Abstract: Key Points• Megakaryocyte-specific Sp1/ Sp3 double-knockout mice display thrombocytopenia, platelet dysfunction, and defects in megakaryocyte maturation.• Selective Mylk inhibition by ML7 affects proplatelet formation and stabilization and ITAM receptor-mediated platelet aggregation.Sp1 and Sp3 belong to the specificity proteins (Sp)/Krüppel-like transcription factor family. They are closely related, ubiquitously expressed, and recognize G-rich DNA motifs. They are thought to regulate generic processes such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 79 publications
1
48
0
Order By: Relevance
“…In control mice, most of these cells were polyploid (>4N) with a 16N population being predominant (~60% of all megakaryocytes) followed by the 8N and 32N populations, each representing 10–20%, and a very low number of 64N cells (Figures 4D and Online Supplementary Figure S2A ), which is in agreement with previous reports. 18,19 Megakaryocytes from Pf4 -Cre Gfi1b fl/fl mice were also polyploid, but had a different distribution: the 32N subset was not affected by Gfi1b loss, the 16N megakaryocytes were notably decreased and the 2N, 4N and 8N fractions were slightly increased compared to controls (Figure 5D and Online Supplementary Figure S2A ). Gating these subsets into a rainbow plot based on their ploidy showed that the increase in smaller megakaryo cytes in the Gfi1b knockout mice was primarily due to an increase in cells of the 2N and 4N subsets (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…In control mice, most of these cells were polyploid (>4N) with a 16N population being predominant (~60% of all megakaryocytes) followed by the 8N and 32N populations, each representing 10–20%, and a very low number of 64N cells (Figures 4D and Online Supplementary Figure S2A ), which is in agreement with previous reports. 18,19 Megakaryocytes from Pf4 -Cre Gfi1b fl/fl mice were also polyploid, but had a different distribution: the 32N subset was not affected by Gfi1b loss, the 16N megakaryocytes were notably decreased and the 2N, 4N and 8N fractions were slightly increased compared to controls (Figure 5D and Online Supplementary Figure S2A ). Gating these subsets into a rainbow plot based on their ploidy showed that the increase in smaller megakaryo cytes in the Gfi1b knockout mice was primarily due to an increase in cells of the 2N and 4N subsets (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Clusters 10 and 51 target an over-abundance of genes with promoter regions containing motifs specific to transcription factors SP1 and NRF1 . Indeed, transcription factor SP1 has recently been shown to regulate platelet formation in mouse [25]. Changes in activities of these transcription factors may mediate the effect of genetic variants in these clusters on platelet formation and dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that the family member miR-29b functions as an oncogene by inhibiting tumor suppressors such as phosphatase and tensin homolog (PTEN) [30]. In this report, we provide evidence that miR-29c regulate MGMT expression indirectly via targeting of transcription factor Specificity Protein 1 (Sp1), a universal zinc finger transcription factor that in expressed in nearly all cells and tissues [31, 32]. We show that the SP1 expression increasing the response to TMZ in glioma cell lines.…”
Section: Introductionmentioning
confidence: 71%